Optimization of Impedance-Based Real-Time Assay in xCELLigence RTCA SP16 Device for the Analysis of Fully Differentiated Caco-2 Cells - Nadia Khan; Magdalena Kurnik-Łucka; Maja Kudrycka; Krzysztof Gil; Gniewomir Latacz (Applied Sciences)
Impedance-based cellular assays allow determination of biological functions of cell populations in real-time by measuring electrical impedance. As compared to end-point assays, such as trans-epithelial electrical resistance assays, for example, they enable fast, non-invasive, and easy detection of cell kinetics—their growth, attachment, and interaction can be monitored over time. In our experiment, Caco-2 cells were cultured on E-plates 16. Next, fully differentiated cells were treated with either TNF-α or 3,4-dihydroxy-L-phenylalanine (L-DOPA). We aimed to verify the possibility of real-time testing of the viability, monolayer formation, and integrity (i.e., the presence of a functional and polarized monolayer) of Caco-2 cells by the xCELLigence real-time cell analyzer (RTCA) S16 system (Agilent Technologies).